The cross-disciplinary perspectives of management : challenges and opportunities - Weber, Yaakov; Vrontis, Demetris; Tsoukatos, Evangelos; Shams, S. M. Riad (Bingley, U.K. : Emerald Publishing Limited, 2019)
Whilst existing studies on research management focus on single disciplinary perspectives in isolation, this new collection integrates a range of theories and business models from multiple fields to offer insights and examples of cross-disciplinary management perspectives. As the workplace environment encounters increased disruption and discontinuity, both researchers and practitioners are facing new and unique managerial challenges. Using alternative research methods from two or more scientific and practitioner disciplines, including Sociology, Politics, Psychology and Technology, the chapters suggest numerous solutions to a wide range of challenges. Some of the challenges explored include: Mind-Genomics and data-driven personalized health plans; the high failure rate of mergers and acquisitions; business ecosystems and start-ups; and, international businesses confronting globalization. Generating innovative research findings, as well as practical managerial solutions, The Cross-Disciplinary Perspectives of Management: Challenges and Opportunities aids both scholars and managers to find solutions to existing managerial challenges across a range of industries and disciplines.
Introduction -- Chapter 1. "Are we there yet?" Mind-genomics and data driven personalized health plans / Gabay Gillie and Moskowitz Howard -- Chapter 2. Mergers and acquisitions: exploitation and exploration / Yaakov Weber -- Chapter 3. Intellectual capital and enabling factors for startups in a business ecosystem / Daniela Rupo, Patrizia Accordino, Elvira Tiziana La Rocca and Tindara Abbate -- Chapter 4. SMEs and globalization / Ilan Bijaou -- Chapter 5. Can a high women quota in supervisory boards influence enterprise success? / Bettina C.K. Binder -- Chapter 6. Implementation of female mentoring programs in German companies: still some way to go / Véronique Goehlich, Briony Gilbertson and Kerstin Bremser -- Chapter 7. Impact of corporate R&D on efficiency in OECD industries / Maria Dos-Santos and Henrique Diz -- Chapter 8. A study of the olive oil consumption and economic sector in the Iberian Peninsula / Carla Lousas, Humberto Ribeiro, Sandra Alves and Cláudia Veloso -- Chapter 9. E-marketing and strategy by energy companies / Felicetta Iovino and Guido Migliaccio -- Chapter 10. The effects of pay dispersion between executives and employees of an organization on firm performance: evidence from Turkey / Aylin Ataay -- Chapter 11. Genuine emotions when facing aggressive customers in the hospitality industry: a conceptual framework / Aspasia Simillidou, Demetris Vrontis and Michael Christofi -- Chapter 12. A retrospective and prospective analysis in the health management through applied innovation / Larisa Mihoreanu -- Index.
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Management; Consolidation and merger of corporations; Business & Economics -- Management; Management: leadership & motivation